Preparation and characterization of encapsulated Burkholderia cepacia UPMB3 - Adzmi, Fariz; Musa, Mohamed Hanafi (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Encapsulation is a process of entrapping an active ingredient to shield it from adverse environmental conditions. Encapsulation of biological control agents (BCAs) enables the creation of a microenvironment wherein the viability of the cell can be maintained during storage, controlled release, and easy delivery. This study aimed to develop an optimum formulation involving the encapsulation of Burkholderia cepacia UPMB3 in alginate and montmorillonite (MMT) clay to improve physical property of the beads and also enhance the viability and shelf life of B. cepacia UPMB3. Encapsulation technique through extrusion process was used to prepare the B. cepacia UPMB3 beads. Alginate was used as carrier while MMT as a filler in order to produce the beads. In liquid form, B. cepacia UPMB3 was found to be easily contaminated, and handling and storage were difficult. This research demonstrates a new direction for the formulation of BCAs for improved cell viability, storage, and delivery.